2016
DOI: 10.18203/2320-1770.ijrcog20162641
|View full text |Cite
|
Sign up to set email alerts
|

Where is the best site for embryo transfer? A study of relation of embryo-fundal distance with pregnancy rate in ICSI-ET cycle

Abstract: Background: Embryo transfer is the ultimate and most critical step of IVF-ICSI treatment cycle. It has a significant impact on the success rate of IVF cycle. Undoubtedly, it has significant impact of the pregnancy rate and implantation rate. Along with the other factors the impact of the site of embryo transfer has also been studied by several investigators. There is lack of clear consensus about the ideal site of embryo transfer. Methods: This study includes a retrospective analysis of 200 embryo transfers do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…14 Tanksale et al in a study reported that clinical pregnancy rates were significantly higher in groups where the transfer distance was between 10-20 mm compared to other groups , the results were similar to our analysis. 15 As shown in Table 4 and Figure 2, the clinical pregnancy rates evaluated in two groups based on the endometrial thickness and estimated that clinical pregnancy rates were found to be slightly higher in group B where the thickness of the endometrium was between 10 and 14 mm. Negative clinical pregnancy rates were found to be higher in group A where endometrial thickness was between 6 mm and 10 mm.…”
Section: Discussionmentioning
confidence: 98%
“…14 Tanksale et al in a study reported that clinical pregnancy rates were significantly higher in groups where the transfer distance was between 10-20 mm compared to other groups , the results were similar to our analysis. 15 As shown in Table 4 and Figure 2, the clinical pregnancy rates evaluated in two groups based on the endometrial thickness and estimated that clinical pregnancy rates were found to be slightly higher in group B where the thickness of the endometrium was between 10 and 14 mm. Negative clinical pregnancy rates were found to be higher in group A where endometrial thickness was between 6 mm and 10 mm.…”
Section: Discussionmentioning
confidence: 98%